2022
DOI: 10.38042/biotechstudies.1159128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some bread wheat (Triticum aestivum L.) genotypes for drought tolerance using SSR and ISSR markers

Abstract: As a result of the rapid increase in the world population, the need for wheat, which is one of the main nutrition in the human diet, is also rapidly increases. However, due to yield losses caused by abiotic stress factors such as drought, wheat production is not sufficient. Therefore, genetic characterization studies performed on wheat genotypes in terms of drought tolerance are important. In this study, genetic characterization of wheat genotypes regardingdrought tolerance was carried out by using molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They reported the reliability and significance of SSR markers in genetic characterization of drought tolerance in bread wheat. Other studies were conducted using 27 bread wheat genotypes to evaluate their response to drought stress through six SSR and eight ISSR markers which they reported significant genetic diversity among the genotypes which could be utilized for marker assisted selection and other breeding programs (Ates-Sonmezoglu et al, 2022). Yadav et al (2018) reported significant variation using 15 ISSR markers for six drought tolerance and six drought sensitive wheat varieties in which 14 markers gave reproductive bands.…”
Section: Resultsmentioning
confidence: 99%
“…They reported the reliability and significance of SSR markers in genetic characterization of drought tolerance in bread wheat. Other studies were conducted using 27 bread wheat genotypes to evaluate their response to drought stress through six SSR and eight ISSR markers which they reported significant genetic diversity among the genotypes which could be utilized for marker assisted selection and other breeding programs (Ates-Sonmezoglu et al, 2022). Yadav et al (2018) reported significant variation using 15 ISSR markers for six drought tolerance and six drought sensitive wheat varieties in which 14 markers gave reproductive bands.…”
Section: Resultsmentioning
confidence: 99%
“…[53] and Özlem et al [54] reported that ISSR markers provided greater recurrence, polymorphism, and the ability to distinguish across bread wheat cultivars.…”
Section: Issr Analysismentioning
confidence: 99%
“…Fifteen SSR markers were utilized in this study. The applied SSR markers were identified from earlier studies based on their consistent association with drought tolerance in wheat [31][32][33]. The sequences of applied primers are detailed in Table 1.…”
Section: Molecular Characterization Of Parental Genotypesmentioning
confidence: 99%